2020 position statement and recommendations of the European Liver and Intestine Transplantation Association (ELITA): management of hepatitis B virus‐related infection before and after liver transplantation. Issue 5 (19th July 2021) - Duvoux, Christophe; Belli, Luca S.; Fung, James; Angelico, Mario; Buti, Maria; Coilly, Audrey; Cortesi, Paolo; Durand, François; Féray, Cyrille; Fondevila, Constantino; Lebray, Pascal; Martini, Silvia; et al.
Summary: Background: Prophylaxis of HBV recurrence is critical after liver transplantation in HBV patients. Despite new prophylactic schemes, most European LT centres persist on a conservative approach combining hepatitis B immunoglobulin (HBIG) and nucleos(t)ides analogues (NA). Aim: This setting prompted the European Liver Intestine Transplantation Association (ELITA) to look for a consensus on the prevention of HBV recurrence. Methods: Based on a 4‐round Delphi process, ELITA investigated 16 research questions and established 50 recommendations. Results: Prophylaxis should be driven according to 3 simplified risk groups: Low and high virological risk patients, with undetectable and detectable HBV DNA pre‐LT, respectively, and special populations (HDV, HCC, poorly adherent patients). In low‐risk patients, short‐term (4 weeks) combination of third‐generation NA+ HBIG, or third generation NA monotherapy can be considered as prophylactic options. In high‐risk patients, HBIG can be discontinued once HBV DNA undetectable. Combined therapy for 1 year is advised. HBV‐HCC patients should be treated according to their virological risk. In HDV/HBV patients, indefinite dual prophylaxis remains the gold standard. Full withdrawal of HBV prophylaxis following or not HBV vaccination should only be attempted in the setting of clinical trials. Organs from HBsAg+ve donors may be considered after assessment of risks, benefits, and patient consent. They should not be used if HDV is present. In poorly adherent patients, dual long‐term prophylaxis is recommended. Budget impact analysis should be taken into account to drive prophylactic regimen. Conclusions: These ELITA recommendations should stimulate a more rational and homogeneous approach to HBV prophylaxis across LT programs. Abstract : De novo prevention of HBV recurrence after liver transplantation for HBV liver disease can be set as follows: in low risk patients, consider long term monoprophylaxis based on 3rd generation nucleos(t)ide analogues (NAs), or long term NAs, combined with short term (4 weeks) hepatitis B immunonoglobulins (HBIG). In high risk patients: consider dual prophylaxis combining NAs + HBIG for 1 year after HBV DNA negativisation, then NAs alone. In special populations: consider long term combination of NAs + HBIG in poorly adherent patients and HDV/HBV patients. In HBV patients with hepatocellular carcinoma (HCC), adjust prophylaxis to the virological risk as in non HCC patients. ​